A high-performance flexible and weavable asymmetric fiber-shaped solid-state supercapacitor enhanced by surface modifications of carbon fibers with carbon nanotubes. Issue 46 (11th November 2016) - Lu, Xiaoyu; Bai, Yang; Wang, Ranran; Sun, Jing
Abstract : A carbon fiber-based positive electrode enhanced by CNT modification with NiCo(OH) x and a negative electrode functionalized with activated carbon were prepared. The supercapacitor showed high energy and power densities. Abstract : To meet the demands of high energy storage and low productive cost as well as the ability to be incorporated into wearable electronics, we developed a flexible and weavable asymmetric fiber-shaped solid-state supercapacitor (a-FSSC) based on carbon fiber bundle@CNT–NiCo(OH) x (CF@CNC) and carbon fiber bundle@activated carbon (CF@AC) electrodes with increased operating voltage (1.4–1.6 V) and capacitance. For the positive electrode of CF@CNC, great electrochemical performance enhancement brought about by surface modifications with air plasma and carbon nanotube (CNT) coating is demonstrated. For the negative electrode of CF@AC, a facile and effective way of incorporating activated carbon into carbon fiber bundles is developed. The resultant assembled a-FSSC showed an areal energy and power density of 33.0 μW h cm −2 and 0.75 mW cm −2 at 1.6 V, which are better than those of most of the present fiber-shaped supercapacitors. The volumetric energy and power density of 0.84 mW h cm −3 and 19.1 mW cm −3 are also comparable to the reported results. Its long cycle life (100% capacitance retention after 8000 charge–discharge cycles) reveals its high electrochemical stability. High capacitance retention in the repeated bending (20% decay after 1000 bending times) and torsion (107% retention after 1000 twisting times) tests demonstrated the great flexibility, structural stability and potential utilization of the a-FSSC in wearable electronics. As a demonstration, a woolen fabric woven with three a-FSSCs connected in series can light a blue LED and be worn on the arm.